Dosežki in načrti v raziskovanju slovenskega izseljenstva po znanstvenih disciplinah po letu 1945 - Klemenčič, Matjaž (Dve domovini, 1993)
This article is concerned with research on the emigration of Slovenes following the Second World War with special regard to the role of historiography in this research. The author of the article concludes that research into Slovene emigration was carried out mainly on an enthusiast level up until the symposium on Louis Adamič which the University of Ljubljana held in 1981.
Keywords: Slovenci; slovenski izseljenci; zgodovinski pregledi